EFFECTIVENESS OF VIDEO-ASSISTED TEACHING MODULE ON REDUCTION OF WEIGHT GAIN BY AEROBIC EXERCISE AMONG OBESE FEMALE COLLEGE - Bhanupriya Das; Niyati Das; Parikshita Khatua (Journal of Mechanics of Continua and Mathematical Sciences)
“Aerobic exercise” is a moderately intense physical activity, which improves your cardio-respiratory fitness and your overall health. A pre-experimental “study” (one group pre-test post-test design) was conducted to assess the effectiveness of a video-assisted teaching module on the reduction of weight gain by aerobic exercise ” among (50) “Obese female students” of “Sashi Bhusan Government Women’s College and City Women’s College (10), Berhampur, Ganjam, Odisha. The objectives of the “study” were to assess the “obesity ” of “Female adolescent college students“ before & after VATM, to evaluate the effectiveness of VATM on the reduction of weight gain by aerobic exercise among obese female students, to find out the association between the post-test measurement score of obese female college students with their selected demographic variables. Data were collected by using a structured demographic variable questionnaire and measurement of height, weight, and BMI schedule. The findings of the study were the mean score & standard deviation value of height were (154.36 ± 5.19) in the pre-test whereas the mean score & standard deviation value of height is (154.36 ± 5.19) in the post-test, the mean score & standard deviation value of weight is (56.78 ± 10.37) in the pre-test, whereas the mean score & standard deviation value of weight is (58.24 ± 12.01) in post-test, the mean score & standard deviation value of BMI is (23.90 ± 4.02) in the pre-test whereas the mean score & standard deviation value of BMI is (24.90 ± 5.02) in posttest respectively. The “P” value of “Demographic Variable wise ” ranges from 0.078 to 0.008. The chi-square (𝜒2) result shows that there was no significant association found between post-test “measurement ” scores when compared to demographic variables. The findings indicate that “VATM” given on “Reduction of weight ” by “Aerobic exercise” was effective.